Identifying and managing patients’ disease risk factors - Wood, Neil (South African Dental Journal, 2022)
Assessing a patient’s risk must be an integral part of any clinical examination, specifically when considering the long-term maintenance of the patient’s oral health once correction and stability have been achieved. We attend to a patient’s immediate need and the main complaint but discount the value of a thorough risk assessment as a long-term investment in a patient’s oral and systemic well-being.